Application of Co-Production in Waste Management Through Waste Banks Program in Batu City - Irkham, Sulung Satriyo; Kamil, Muhammad; H, Saiman (Government Studies of Muhammadiyah Malang University/AIPPTM, 2019)
The problem of waste in Batu City can threaten tourism sector in this city. The Waste Management System Program is held by the Environment Agency (DLH) Batu City seems to be unable to access waste problems in the upstream sector, particularly household waste from residential settlements. This lack capacity of the program followed up by DLH by organizing a waste bank program through the establishment of the Community Waste Bank (KBS) Kartini Sejati which coordinated around 60 waste banks in Batu City to be involved in waste management.This study aims to explain the involvement of KBS Kartini Sejati in waste management in co-production and the obstacles faced by it. The concept of co-production refer to an alternative concept in the implementation of public services where implementation focuses on the dominant role of the community, while the government or other parties such as the private sector are only facilitators. This research use qualitative method by utilizing data from observations, interviews and documentation. The results of this study indicate that KBS Kartini Sejati in several of its activities which include training in waste management, waste management, and